Downregulation of hsa_circRNA_0001400 Helps to Promote Cell Apoptosis Through Disruption of the circRNA_0001400–miR-326 Sponge in Cervical Cancer Cells - Cai, Yantao; Li, Chuyu; Peng, Fang; Yin, Shuanghong; Liang, Huiyi; Su, Jiyan; Li, Lin; Yang, Anping; Liu, Hui; Yang, Chuansheng; Luo, Dixian; Xia, Chenglai (Frontiers in Genetics, 2021)
Background:In recent years, circular RNAs (circRNAs) have been reported to serve as essential regulators in several human cancers. Nevertheless, the function and mechanism of circRNAs in cervical cancer remain elusive. Methods:Flow cytometry assays were performed to measure cell apoptosis and cell cycle. Colony Formation and transwell chamber were performed to measure cell migration and invasion. Double luciferase reporter for gene analysis was used to detect the interaction between hsa-circRNA_0001400, miR-326, and Akt. Relative protein levels were determined by immunoblotting and relative gene levels were determined by quantitative real-time PCR. Tumor Xenograft Modeling was used to evaluate the effect of hsa_circRNA_0001400_siRNA in vivo. Results:In the present study, we showed that hsa_circRNA_0001400 was highly expressed in cervical cancer tissues relative to in matched normal tissue. We found that hsa_circRNA_0001400_siRNA significantly promoted the apoptosis of cervical cancer cells and arrested the cell cycle and migration of cervical cancer cells. We showed that hsa_circRNA_0001400_siRNA can inhibit the protein expression of Akt and that the inhibition of miR-326 could rescue the inhibition of Akt in cervical cancer cells. We found that has-miR-326 was downregulated in cervical cancer tissues and hsa_circRNA_0001400_siRNA could increase the gene expression of has-miR-326. We also observed that hsa_circRNA_0001400_siRNA inhibited the growth and angiogenesis of SiHa xenografts in nude mice. Conclusions:In conclusion, this study provides evidence that the hsa_circRNA_0001400–miR-326–Akt network promotes cervical cancer progression. Notably, our findings demonstrate the novel antitumor effects of hsa_circRNA_0001400_siRNA in cervical cancer.